Penyalahgunaan Wewenang oleh Oknum Dukun pada Masyarakat Sunda Jawa Barat - Tubagus Ronny Nitibaskara (Antropologi Indonesia, 1997)
It has long been known that there are many traditional healers in West Java, who conduct their practice openly as well as in disguise. Besides many traditional healers who are beneficial for their patients, there are also those who are harmful, because they practice forgery, blackmail and even rape. This article aims to present the cases of power abuse, which complied and analyzed from qualitative research, carried out towards several traditional healers in West Java. The result of the study shows that there are many victims caused by some traditional healers, who own one of the authorities, namely charismatic authority.